How is the correlation between Halal Certification and the Growth of Indonesia’s Export Economic Value? - Aini, Nur; Go, Riska Tezara (Halal Research Journal, 2025)
Indonesia, as the country with the largest Muslim population in the world, holds immense potential to lead the global halal sector. Efforts to accelerate halal certification, particularly in the food, beverage, and cosmetics industries, have yielded positive outcomes. By mid-2023, 38,480 products had obtained halal certification, driven by initiatives like the Free Halal Certification (Sehati) program and national campaigns. Halal certification not only serves as a legal requirement but also enhances product competitiveness in domestic and international markets. However, despite the projected global halal market size of USD 2.3 trillion by 2024, Indonesia's contribution remains relatively small compared to countries like Malaysia and the United Arab Emirates. This study investigates the correlation between halal certification issuance and export value, revealing a weak negative correlation, with the export value of halal products declining in 2023 due to global economic challenges. The findings underscore the importance of addressing external factors and adopting a comprehensive approach, involving both government and businesses, to enhance Indonesia's halal export performance and ensure long-term growth.